Prokaryotic Chaperonins as Experimental Models for Elucidating Structure-Function Abnormalities of Human Pathogenic Mutant Counterparts - Conway de Macario, Everly; Robb, Frank T.; Macario, Alberto J. L. (Frontiers in Molecular Biosciences, 2017)
All archaea have a chaperonin of Group II (thermosome) in their cytoplasm and some have also a chaperonin of Group I (GroEL; Cpn60; Hsp60). Conversely, all bacteria have GroEL, some in various copies, but only a few have, in addition, a chaperonin (tentatively designated Group III chaperonin) very similar to that occurring in all archaea, i.e., the thermosome subunit, and in the cytosol of eukaryotic cells, named CCT. Thus, nature offers a range of prokaryotic organisms that are potentially useful as experimental models to study the human CCT and its abnormalities. This is important because many diseases, the chaperonopathies, have been identified in which abnormal chaperones, including mutant CCT, are determinant etiologic-pathogenic factors and, therefore, research is needed to elucidate their pathologic features at the molecular level. Such research should lead to the clarification of the molecular mechanisms underlying the pathologic lesions observed in the tissues and organs of patients with chaperonopathies. Information on these key issues is necessary to make progress in diagnosis and treatment. Some of the archaeal organisms as well as some of the bacterial models suitable for studying molecular aspects pertinent to human mutant chaperones are discussed here, focusing on CCT. Results obtained with the archaeon Pyrococcus furiosus model to investigate the impact of a pathogenic CCT5 mutation on molecular properties and chaperoning functions are reviewed. The pathogenic mutation examined weakens the ability of the chaperonin subunit to form stable hexadecamers and, as a consequence, the chaperoning functions of the complex are impaired. The future prospect is to find means for stabilizing the hexadecamer, which should lead to a recovering of chaperone function and the improving of lesions and clinical condition.